L’expérience du service de néonatologie et de chirurgie générale dans la prise en charge des péritonites chez l’enfant durant la période 2018 - 2022 - HADJKOUIDER Souheir; -CHELGUI Hasna (UNIVERSITE AMAR TELIDJI LAGHOUAT, 2023)
Peritonitis is defined as acute inflammation of the peritoneal serosa with or without infection. This is a work that includes a retrospective and prospective analysis of a series of 83 children treated for acute peritonitis at the level of the neonatology department at the EHS HAKIM Saadane and the general surgery department of the EPH BEN ADJILA Ahmida from 2018 to 2020 and the mixed hospital BEN DEGHINE Ali during the period from January 1, 2018 until December 31, 2022. The median age is 9.12 years, with extremes of 1 day and 16 years, and a predominance in the male subject. It was found that children operated for acute peritonitis of urban origin (75.9%) exceeded that of children of rural origin (24.1%). The diagnosis is clinical, of which the pain with the contracture are the alarm signs. The general signs are dominated by fever. The physical examination is essential. The NFS, the ultrasound are systematic examinations carried out in all our patients. The etiological diagnosis is mainly dependent on the age of the child. The etiologies are varied, dominated in our context by: - Appendicular peritonitis in 90.4%. - Hollow organ perforation in 4.8%. - Postoperative peritonitis in 2.4%. - Laparoschisis in 2.4%. The postoperative course was simple in the majority of cases (86.6% of cases) in However
72 p.